Navigating innovation success through projects: Role of CEO transformational leadership, project management best practices, and project management technology quotient - Umer Zaman; Shahid Nawaz; Raja Danish Nadeem (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In an advancing project-based global economy, the ability to leverage innovation, and the adoption of disruptive technologies are critical for product and process innovation success. This study makes the initial attempt to examine the effects of CEO transformational leadership (CTL), project management best practices (PMBP), and project management technology quotient (PMTQ) on multi-dimensional innovation success. Drawing on data of 261 practitioners in the information and communications technology industry in South Korea, the hypothesized relationships were tested using higher-order partial least squares structural equation modeling (PLS-SEM). The study finds supportive evidence on the positive effects of CTL, PMBP, and PMTQ on innovation success. Moreover, PMBP and PMTQ demonstrated a significant moderating influence on the relationship between CTL and innovation success. Besides the development and validation of a new PMTQ scale, the study findings offer novel theoretical predictions, methodological contributions, and implications for practitioners to mitigate the challenges of successful innovations.
Keywords: 650; CEO transformational leadership; innovation success; project management best practices; project management technology quotient